Job commitment, total quality management, information communication technology adoption and work-related stressors: A conceptual framework for student satisfaction - Koomson, Samuel (Utan Kayu Publishing, 2022)
This paper aim to examine the direct effect of job commitment (JCT) on student satisfaction (SST), exploring the mediating roles of total quality management (TQM) and information communication technology adoption (ADT), and moderating roles of work-related stressors: toxic leadership (TLE) and job demands (JDD). The paper develops a conceptual framework along with postulations by combining both empirical and theoretical literature multidisciplinary fields. This paper proposes that JCT will be positively related to SST, and this positive relationship will be mediated by TQM and ADT. Additionally, work-related stressors: TLE and JDD will moderate the direct positive effect of JCT on SST. This paper provides implications for both researchers and practitioners in the areas of strategic decision-making and stress management in educational institutions for enhancing SST by applying JCT, TQM and ADT as strategic tools, while keeping work-related stressors: TLE and JDD under control. It lays the foundation for upcoming researchers to empirically test this conceptual framework in different educational settings. By boosting employees’ JCT, educational institutions stand the chance of improving SST via TQM and ADT. Additionally, JCT can foster SST under a working environment where work-related stressors: TLE and JDD are kept low. The paper offers unique insights into how TQM and ADT connect JCT to SST, and how JCT relates to SST under work-related stressors: TLE and JDD. It also highlights the theoretical contributions of the resource-based theory of a firm, affective events theory, and activation theory.